Non-pharmacological interventions for delirium in critically ill children: a scoping review - Zilezinski, Max; Denninger, Natascha-Elisabeth; Tannen, Antje; Kottner, Jan (BMJ open, 2025)
Objectives: Delirium is one of the most common forms of acute cerebral dysfunction in critically ill children, leading to increased morbidity and mortality. The aim was to identify studies describing or evaluating non-pharmacological interventions to prevent or treat paediatric delirium. Design: Scoping review. Data sources  Searches were performed in Medline, CINAHL, Cochrane Library, Ovid (Journals), EMBASE and Web of Science from January 2000 to April 2023. A hand search and update were conducted on 01 June 2024. Eligibility criteria for selecting studies: We included studies involving critically ill children (0-18 years) in intensive care settings that examined non- pharmacological interventions for the prevention or treatment of paediatric delirium. Only empirical studies and reviews with transparent methodology were considered. Data extraction and synthesis: Title and abstract screening and full-text review of articles were conducted by two reviewers based on prespecified inclusion criteria. Two reviewers extracted relevant information from the included studies in tabular form. Extracted variables included publication year, title, author(s), country, setting, population and age, design, sample size, intervention components, outcome(s) and findings. - Results: Nine studies were included. In total, 16 different intervention components were identified. The most frequently reported components for preventing and treating paediatric delirium were promoting mobilisation, encouraging family presence and involvement, improving sleep, and standardised instruments or checklists for underlying aetiology. Most intervention studies were before-and-after studies; overall, seven different outcomes were used. Study results regarding the effects of delirium were inconsistent. - Conclusions: Various non-pharmacological interventions are currently described to mitigate paediatric delirium, but the underlying evidence is limited. High-quality intervention research using relevant and comparable outcomes is needed to evaluate the effect of non-pharmacological interventions. Despite employing a comprehensive search strategy, we must consider the possibility that relevant articles were overlooked.
Gesehen am 19.02.2026